Ultimate Guide to Insulin - Zaman, Gaffar (IntechOpen, 2019)
The book presents a qualitative and quantitative approach to understand, manage and enforce the integration of insulin into diabetes mellitus. Utilizing a sound theoretical and practical foundation and illustrating procedural techniques through scientific examples, the book bridges the gap between insulin and diabetes mellitus management. Detailed procedures have been omitted because of the variety of equipment and commercial kits used in today's clinical laboratories.